Associations Between Spirituality, Meaning in Life, and Depressive Disorders Among a Sample of Individuals in Treatment for Substance-Use Disorders. Issue 4 (1st October 2016) - Horton, E. Gail; Luna, Naelys; Malloy, Tammy
ABSTRACT: This study explored the relationships between spirituality (existential purpose and meaning and religious well-being), meaning in life (presence and search), and three mood disorders among individuals in residential treatment for substance-use disorders. Results indicated that existential well-being was a significant predictor of both for major depressive disorder and dysthymia symptomatology. Religious well-being and search for meaning in life were significant predictors of bipolar symptomatology. Thus, development of purpose and meaning in life is indicated for co-occurring major depressive disorder or dysthymia and substance abuse, while finding support in a religious community may benefit those with co-occurring bipolar disorder.